Development of heterotic hybrids of sweet corn for green ear yield and other component traits (Bangladesh Journal of Botany, 2023)
Forty two experimental hybrids generated through full diallel mating were evaluated in Randomized Block Design during kharif 2019 to study the magnitude of heterosis in sweet corn. Mid-parent heterosis ranged from -21 to 258 for DEW; -25 to 2 for GFW; 3 to 229 for GEY and standard heterosis ranged from 2.13 to 134.95 for DEW; 82.93 to 317.07 for GFW; -15.70 to 68.40 for GEY. Green ear yield exhibited positive significant correlation of mid-parent and commercial heterosis with NKPR, DEW and GFW in common, while no significant association between GEY and TSS was observed. The crosses KH1831 × SC Syn, SC Syn × SC Sel 2 and SC Sel 2 × SC Syn manifested highest mid-parent heterosis for de-husked ear weight, green ear yield and green fodder weight thus utilizing these hybrids in breeding programmes will serve for dual purpose of yield with fodder.Bangladesh J. Bot. 52(4): 999-1005, 2023 (December)